Development and Evaluation of Android-based Infrastructure Rental Application: A Design Science Research Approach - Kandami, Joshua Hans; Inan, Dedi Iskandar; Juita, Ratna; Baisa, Lorna Yertas; Sanglise, Marlinda; Indra, Muhamad (Jurnal Teknologi dan Manajemen Informatika, 2024)
This study developed and evaluated a mobile application for infrastructure rental at the Quality Assurance Agency for Education (BPMP) in West Papua using the Design Science Research (DSR) approach in the field of Information Systems (IS). This application, the first designed specifically for the needs of BPMP West Papua and integrated with the existing system, was assessed based on usability and user acceptance through interviews, black box testing, and effectiveness testing using Structural Equation Modeling (SEM) with the Technology Acceptance Model (TAM) approach. The black box testing results indicated successful application development. Evaluation with 64 respondents through hypothesis testing showed that social influence and technological anxiety significantly affect attitudes toward accepting the use of the application. This highlights the importance of considering these factors for the successful implementation of the mobile application at BPMP West Papua, potentially enhancing the efficiency of infrastructure rental.